Analysis of ChatGPT Adoption using the UTAUT Model - Galantry, Lisa Amelia; Tanaamah, Andeka Rocky (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
In the current digital era with information technology is developing rapidly in various fields. Especially in all human work that requires working quickly with maximum results. many innovations have emerged, one that currently popular is Artificial Intelligence (AI). One of the popular AI currently is ChatGPT, with many of ChatGPT's users, including students. This research contains what factors that influence interest in using ChatGPT, especially among students, with a case study focusing on undergraduate students of Information Systems at Satya Wacana University. The aim is to identify the factors influencing students in using ChatGPT for both learning and daily activities, The Unified Theory of Acceptance and Use of Technology (UTAUT) model is being used in this study. The results of this research show that the acceptance of ChatGPT among Undergraduate Students of Information Systems at Satya Wacana Christian University. Performance expectancy and Facilitating conditions are factors that influence the intention to use ChatGPT. Then there is behavioral intention shows that the intention to use also influences user behavior.